Case study: company analysis Froogurtz / Nik Farhana Amirah Nik Azman … [et al.] - Nik Azman, Nik Farhana Amirah; Rohaizad, Siti Nuraisyah; Mohd Rafi, Nadia Syakirah; Mohd Faizal, Fatini Irdina; Ibrahim, Nurain Aqilah; Mohd Nizam, Sara Irdina (2023)
Froogurtz is a frozen yogurt company based in Malaysia, known for its high-quality and nutritious yogurt products. With its unique recipe and carefully sourced ingredients, Froogurtz aims to provide customers who prioritize their health with a delightful frozen yogurt experience. Established in 2020 by Mohamad Hafizuddin Che Soh, Froogurtz quickly gained popularity due to its delicious offerings and creative toppings. The company's vision is to become the leading provider of healthy and tasty frozen yogurt in Malaysia, offering a wide range of flavors and toppings to suit every customer's preference. Its mission is to consistently deliver exceptional products and excellent customer service, while promoting the benefits of yogurt as a nutritious treat. Through its innovative approach and commitment to quality, Froogurtz has successfully positioned itself as a trusted brand in the yogurt industry, attracting a loyal customer base and driving its growth in the market. Next, this case study involves the key findings related to the business, marketing, and operational strategies of Froogurtz. The business strategy revolves around offering high-quality and nutritious frozen yogurt to health-conscious individuals. The company follows a franchise business model to expand quickly while maintaining quality standards. The marketing strategy emphasizes the health benefits of Froogurtz's products, utilizing social media platforms such as TikTok to engage with customers. The operational strategy focuses on quality management, schedule management, and yogurt machine processes to ensure consistent product quality and customer satisfaction. In addition, the signature product of Froogurtz is yogurt, which is made with high-quality ingredients and topped with various toppings such as fresh fruits, cereals, and sauces. The cafe also offers a range of other drinks such as milkshakes, coffee, frappes, and smoothie yogurts. Froogurtz aims to provide a halal and affordable option for customers, with a focus on customer service and a peaceful environment. Moreover, in this case study highlights the financial achievements of Froogurtz, stating that the company's profits have been increasing as more people become aware of its products. Despite initial challenges due to the COVID-19 pandemic, the owner's innovative marketing approach has contributed to the rapid increase in product demand. The monthly direct selling sales of the company range around RM100,000. Furthermore, there are a few recommendations for Froogurtz to improve their product quality. It suggests continuing the focus on product quality and customer service while expanding the marketing efforts to reach a wider audience. The company can consider collaborating with influencers or running promotional campaigns to increase brand awareness. It is also recommended to explore opportunities for expanding into new locations and diversifying the product offerings to attract a broader customer base. Overall, the recommendations aim to support Froogurtz's growth and success in the frozen yogurt industry.